2014
DOI: 10.1371/journal.pone.0095011
|View full text |Cite
|
Sign up to set email alerts
|

High Temperature and Salinity Enhance Soil Nitrogen Mineralization in a Tidal Freshwater Marsh

Abstract: Soil nitrogen (N) mineralization in wetlands is sensitive to various environmental factors. To compare the effects of salinity and temperature on N mineralization, wetland soils from a tidal freshwater marsh locating in the Yellow River Delta was incubated over a 48-d anaerobic incubation period under four salinity concentrations (0, 10, 20 and 35‰) and four temperature levels (10, 20, 30 and 40°C). The results suggested that accumulated ammonium nitrogen (NH4 +-N) increased with increasing incubation time und… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(20 citation statements)
references
References 44 publications
1
18
0
Order By: Relevance
“…(14) also indicated that µ w1 showed an increasing trend with increasing salinity level. Therefore, we considered that although salinity could reduce µ w1 , an extremely high soil salinity level (> 24.42 dS·m -1 ) might increase µ w1 because of the increased ammonium-nitrogen adsorption with soil salinity, and similar results were obtained in the studies of Noe et al [36] and Gao et al [37].…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…(14) also indicated that µ w1 showed an increasing trend with increasing salinity level. Therefore, we considered that although salinity could reduce µ w1 , an extremely high soil salinity level (> 24.42 dS·m -1 ) might increase µ w1 because of the increased ammonium-nitrogen adsorption with soil salinity, and similar results were obtained in the studies of Noe et al [36] and Gao et al [37].…”
Section: Discussionsupporting
confidence: 67%
“…Nkrumah et al [42] noted that urea required a significant amount of time to transform into nitrogen, especially in irrigation conditions. In addition, both Gao et al [37] and Khoi et al [21] observed that the adverse effects of salinity on nitrogen mineralization were short-lived, whereas the rate of nitrogen mineralization recovered in later periods. Thus, a long incubation time is necessary in future studies to confirm this aspect.…”
Section: Discussionmentioning
confidence: 97%
“…It was found that increased salinity may also support mineralization of nitrogen (NH 4 + -N a NO 3 -N) in soils [22][23]. Pathak and Rao [13] report that nitrogen mineralization may continue despite the microbial activity being supressed by the presence of salts.…”
Section: Resultsmentioning
confidence: 99%
“…As the main elements supporting life on earth system, the C, N, P, S cycles in soil have been altered by human activity through land-use change, agricultural intensification, and use of fossil fuels (Vitousek et al 1997;Matson and Vitousek 2006;Stevenson et al 2010;Song and Liu 2013;Liu et al 2012). With improved knowledge of how human activity affects the C, N, P, S cycles in soil, recommendations for safety of human health, other living organisms, and natural ecosystems might be improved (González-Chávez et al 2010;Bai et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Harrison-Kirk et al (2014) evaluated the response of C and N fractions to dry-wet cycles and their availability as substrates for C and N mineralizations along a SOM gradient in two soils of differing textures. González-Chávez et al (2010) determined the effects of long-term (25 years) no-till and conventional tillage management and cropping sequence and a rotation of sorghum, wheat, and soybean on soil microbial community structure and labile and recalcitrant microbial bioproducts related to soil C, N, and P pools in central Texas. Bejarano et al (2014) determined the impact of elevated N input on C and N dynamics in soils collected from three mature seasonally dry tropical forests (SDTF) along a precipitation gradient in Yucatan (Mexico).…”
Section: Introductionmentioning
confidence: 99%